2022
DOI: 10.3390/d14121076
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Suitability of Eastern Sarus Crane (Antigone Antigone sharpii) in Ayeyarwady Delta, the Union of Myanmar

Abstract: The eastern sarus crane (Antigone antigone sharpii; ESC) is a species related to wetland ecosystems in Southeast Asia. The habitat suitability of the eastern sarus crane in Ayeyarwady Delta was surveyed between March 2018 and February 2019. Eastern sarus cranes were found at 73 locations and Maximum Entropy (MaxEnt) was used to classify the habitat suitability among different seasons. MaxEnt showed the largest total area of highly suitable habitat was in the winter season (2450 km2, AUC = 0.968), while the lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Two papers in our first volume use such modelling approaches. In the first of these papers, Latt et al [2] use SDMs to identify suitable habitats and the key environmental factors that influenced the distribution of suitable habitat areas for the Eastern Sarus Crane (Antigone antigone sharpie) populations in the ~82,000 km 2 Ayeyarwady Delta Region in Myanmar, an area widely suspected to be one of the most important areas for the sarus crane in the country. Their models revealed that the lower part of the Ayeyarwady Delta is currently suitable for supporting cranes throughout all seasons and that the species is often found in close proximity to human settlements.…”
mentioning
confidence: 99%
“…Two papers in our first volume use such modelling approaches. In the first of these papers, Latt et al [2] use SDMs to identify suitable habitats and the key environmental factors that influenced the distribution of suitable habitat areas for the Eastern Sarus Crane (Antigone antigone sharpie) populations in the ~82,000 km 2 Ayeyarwady Delta Region in Myanmar, an area widely suspected to be one of the most important areas for the sarus crane in the country. Their models revealed that the lower part of the Ayeyarwady Delta is currently suitable for supporting cranes throughout all seasons and that the species is often found in close proximity to human settlements.…”
mentioning
confidence: 99%